Teka wojenna Franciszka Chrząstowskiego. Z kolekcji graficznej Biblioteki Śląskiej (PDF 4,36 MB) (Książnica Śląska, 2025)
The article describes the latest graphic acquisition of the SilesianLibrary – “Teka wojenna (Portfolio of the War) 1914–1915” madeby students of the 1st c. k. Realschulle in Lviv under the supervision of Prof. Chrząstowski. The article discusses the lithographs ofstudents and presents the figure of the professor of drawings Franciszek Chrząstowski, the initiator of the creation of the portfolioand the artist-pedagogue responsible for the process of its creation.The ownership mark (ex-libris by Zbigniew Jozwik) placed in the album and made for the Warsaw bibliophile, collector and numismaticof Lech Kokocinski was also described. The author of the paper triedto decipher the manuscript entry on the title card of the portfolio.This interesting publication is a valuable addition to the bibliophilecollection of Roman Chrząstowski (son of Franciszek), which is inthe collection of the Silesian Library.